Proceedings of the 7th International Conference on Systematic Innovation - ICSI 2016 - Machado, Virgílio António Cruz (2017)
It is our pleasure to welcome you at the 7th International Conference on Systematic Innovation. It is our objective to provide a forum for the discussion and dissemination of recent advances in the field of TRIZ Methodology, Knowledge-Based and Systematic Innovation. The goal is to enable practitioners, researchers and scientists to exchange ideas on the these topics and to provide an international forum for exchanging new ideas and recent achievements by the TRIZ community and enabling further advances and collaboration with the industrial community. We wish to express our sincere gratitude to the members of the organizing, scientific and technical committees. The reviewers of the papers had a very important job, contributing significantly to the success of the conference. We also wish to express our thanks to our invited speakers. Very special thanks to our students, sponsors and to all who helped us with logistics, conference website, and publications. Welcome to Portugal and Lisbon. We hope you all have a very happy and rewarding meeting.